Laboratory evaluation of the effect of waste plastic bottle (PET) on rutting performance of hot mix asphalt mixtures. (2nd May 2016) - Ziari, Hassan; Kaliji, Arman Ghasemi; Babagoli, Rezvan
ABSTRACT: The authors aim to evaluate the effects of using waste polyethylene terephthalate (PET) as a modifier on properties of asphalt mixtures. The rutting performance of asphalt mixtures that include various percentages of PET (0%, 0.25%, 0.5%, 0.75%, 1%) and various PET sizes (10 × 2.5, 20 × 2.5, and 30 × 2.5 mm) were evaluated through dynamic creep test and Hamburg wheel tracking device. Results indicated that the rutting resistance of mixtures increases by addition of PET contents and decreases with increase in PET sizes.